Real-world healthcare resource utilization and costs associated with tisagenlecleucel and axicabtagene ciloleucel among patients with diffuse large B-cell lymphoma: an analysis of hospital data in the United States. Issue 9 (29th July 2022) - Maziarz, Richard T.; Yang, Hongbo; Liu, Qing; Wang, Travis; Zhao, Jing; Lim, Stephen; Lee, Soyon; Dalal, Anand; Bollu, Vamsi
Abstract: This study compared the real-world healthcare resource utilization (HRU), costs, adverse events (AEs), and AE treatments associated with the chimeric antigen receptor T-cell (CAR-T) therapies, tisagenlecleucel (tisa-cel) and axicabtagene ciloleucel (axi-cel), for relapsed/refractory diffuse large B-cell lymphoma (r/r DLBCL). Adults with DLBCL who received tisa-cel or axi-cel were identified in the Premier Healthcare Database (2017–2020). Non-CAR-T costs, HRU, and AE rates during the infusion and follow-up periods were compared between the tisa-cel and axi-cel cohorts. Of 119 patients, 33 received tisa-cel (86% as inpatient infusion) and 86 received axi-cel (100% inpatient). Tisa-cel was associated with significantly shorter mean inpatient length of stay than axi-cel during infusion (11.3 vs. 18.3 days) and follow-up ([monthly] 3.9 vs. 6.9 days). Non-CAR-T costs were significantly lower for tisa-cel compared with axi-cel during infusion (27594.8 vs. 51378.3) and follow-up ([monthly] 28777.3 vs. 46575.7; both p < .05). Rates of AEs and AE treatments were similar.